THE EFFECT OF ONLINE PROMOTION, PRICE. AND PACKAGING ON SALES COMPETITIVENESS OF CULINARY PRODUCTS IN AMBON CITY AGAINST THE COVID-19 PANDEMIC - Silfiena Siahainenia; Erlinda Tehuayo; Grace H. Tahaparry (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
The research aims to analyze the effect of online promotion, price, and packaging on sales competitiveness. The number of respondens are 100 peoples and the sampling method is purposive sampling in which the sampling are businessmen who live in Batu Gajah, Waihaong, Benteng, and Batu merah Village, Ambon City. The research instrument uses Likert Scale to measure the response of respondents. The analysis tool used is multiple regression. The results show that online promotion, price, and packaging have a posititif effect on sales competitiveness.